The Mortality and Medical Costs of Air Pollution: Evidence from Changes in Wind Direction - Deryugina, Tatyana; Heutel, Garth; Miller, Nolan H; Molitor, David; Reif, Julian (The American economic review, 2019)
We estimate the causal effects of acute fine particulate matter exposure on mortality, health care use, and medical costs among the US elderly using Medicare data. We instrument for air pollution using changes in local wind direction and develop a new approach that uses machine learning to estimate the life-years lost due to pollution exposure. Finally, we characterize treatment effect heterogeneity using both life expectancy and generic machine learning inference. Both approaches find that mortality effects are concentrated in about 25 percent of the elderly population.